Effect of SO42− and Cl− anionic attack on the localized corrosion resistance and morphology of 409 ferritic stainless steel - Roland Tolulope Loto (Results in Physics, 2019)
The corrosion polarization behaviour and optical characterization of 409 ferritic stainless steel (SS409) in 0.25 M H2SO4 (at specific NaCl concentration), 0.375 M H2SO4 and 0.5 M H2SO4 was evaluated with potentiodynamic polarization technique, open circuit potential measurement and optical microscopy characterization. Results showed the SS409 corrosion rate is proportional to the concentration of SO42− and Cl− anions in the electrolyte. At 0.25 M H2SO4, SS409 corroded at a rate of 7.29 mm/y; addition of 0.125% NaCl accelerated the corrosion rate to 16.75 mm/y coupled with a corresponding increase in corrosion current density from 6.71 × 10−4 Acm2 to 3.08 × 10−3 Acm2. Further increase in Cl− anion concentration to 0.75% NaCl increased the corrosion rate to 19.49 mm/y. At 0.25 M H2SO4 the pitting current value is 1 × 10−4 A, this value increased to 1.03 × 10−4 A at 0.25 M H2SO4 (0.125% NaCl) and 8.40 × 10−4 A at 0.25 M H2SO4 (0.5% NaCl). Beyond 0.5% NaCl, passivation behavior was completely absent. Intergranular cracks, large macro-pits and numerous micro-pits were observed for SS409 from 0.25 M H2SO4 (0.75% NaCl) due to Cr depletion and dissolution of inclusions. SS409 from 0.5 M H2SO4 showed the presence of deepened intergranular cracks, shallow pits and a deteriorated surface due to the action of SO42− anions. The morphology of SS409 in 0.25 M H2SO4 + 0.125% NaCl showed slight deterioration in addition to enlarged micro-pits. Keywords: Pitting, Corrosion, Intergranular, Chloride, Anions